A Personal Journey of Being an Expat - Lester Wills (The Pinnacle)
In 2023, I contributed to a book on Global Leadership, reflecting on my personal journey as an expat. Invited to join a global leadership program, I moved from the UK to Australia in 1987, aiming for professional growth and cultural enrichment. While the career opportunities were promising, the reality brought significant personal and emotional challenges, particularly the strain on family relationships. Initially filled with excitement, my family and I faced daunting logistics, from securing visas to adapting to a new environment.